Teacher Preparation According to Modern Educational Trends - Arhim, Ibrahim Othman; Al-Shuhubi, Hassan Salem ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2016)
The study aimed to identify the essential conditions and requirements for a teacher’s success, explore modern mechanisms for teacher preparation and training, examine teacher education models in developed countries, and propose strategies for improving teacher development. The researchers adopted the descriptive-analytical method due to its suitability for analyzing the current context and gathering relevant data. The findings revealed two key pillars for successful teacher preparation: first, restoring the teacher’s self-confidence as a messenger with a mission rather than a job seeker; second, rebuilding societal trust in the teacher’s role as a respected social leader and role model. The study also emphasized the importance of setting clear, long-term goals and strategies to ensure sustainable progress in teacher training.